A new species of Xiphovelia Lundblad, 1933 and notes on Pseudovelia Hoberlandt, 1950 (Heteroptera: Veliidae) from Vietnam - Ye, Zhen; Bu, Wenjun (Zootaxa, 2016)
The genus Xiphovelia Lundblad is recorded for the first time from Vietnam and X. vietnamica sp. nov. is described as new. Photographs of the male and female dorsal habitus, male legs, and male genitalic structures are provided. Pseudovelia vittiformis Ye, Polhemus & Bu, 2013 and P. tibialis tibialis Esaki & Miyamoto, 1955 are newly recorded from Vietnam. Together with two other species of Pseudovelia Hoberlandt from southern Vietnam, four species of Pseudovelia are now known from the country. A distribution map for the species of Xiphovelia and Pseudovelia occurring in Vietnam also is provided.